ANALYSIS OF INCOME OF ORNAMENTAL PLANT RENTAL BUSINESS (CASE STUDY CV. GREEN SAUJANA NURSERY, DEPOK CITY, WEST JAVA) - Elpawati Elpawati; Junaidi Junaidi; Nuriyanti Pratami (Syarif Hidayatullah State Islamic University Jakarta, 2020)
A business which is quite potential is the development of an ornamental plant rental business on CV. Green Saujana Nursery can be run and on the one hand, it looks quite profitable financially. However, the company has not conducted periodic financial evaluations, so the profits generated by the company are not visible. In business development, income is very important because it is a benchmark for the success of a business, so in its implementation, it is necessary to have good financial management so that the company's goals can be achieved.This study aims to: Find out the costs incurred by the Green Saujana Nursery company. Knowing the amount of income for the ornamental plant rental business in CV. Green Saujana Nursery. Knowing the level of R/C Ratio, Net B/C Ratio, and Payback Period (PP) in the ornamental plant rental business in CV. Green Saujana Nursery.The study used primary and secondary data. Primary data were obtained through interviews with related parties CVs. Green Saujana Nursery in the form of technical and non-technical business data. Secondary data is obtained from company documents such as ornamental plant catalogs for plant rental businesses, and company financial statements such as data on costs incurred and receipts from ornamental plant rental businesses, on CV. Green Saujana Nursery in 2018. Quantitative data is processed using the Microsoft excel 2013 program.The results showed that, the advantages of the ornamental plant rental business in CV. Green Saujana Nursery in 2018 amounted to Rp. 493,918,058 which resulted from a reduction in the value of receipts of Rp. 895,655,000 with a total cost of Rp. 401,736,942. The largest variable costs are labor costs and operational material costs for the purchase of orchids amounting to Rp 153,480,000. The sustainability of the ornamental plant business can be seen from the value of the R / C Ratio and B / C Ratio which produces a value greater than one, so the ornamental plant rental business provides decent profits for CV companies. Green Saujana Nursery. The value of the Payback Period of the plant rental business in CV. Green Saujana Nursery is 0.2 years. Based on these values, it can mean that the ornamental plant rental business in CV. Green Saujana Nursery, can return investment capital in a relatively short time, which is 2 months.